Why the Rate of Return of Religious School (Madrasah) is Too Low: The Case in Indonesia - Elfindri, Elfindri; Ariyanto, Edi; Maryati, Sri; Sari, Delfia Tanjung (UI Scholars Hub, 2022)
Religious schools (madrasah) in Indonesia have contributed to fulfilling the equity goals of education. Up to this point, studies on the rate of return of madrasah and its relation to general or vocational education remain limited. In contrast to the previous studies that omit madrasah from their analysis, this study pay greater attention to this particular type of education. By adopting the Mincerian model of the human capital and applying the semi-log earnings function to the 2012 data of the National Socioeconomic Survey (SUSENAS) of Indonesia, this study discovers that the rate of return of graduates from madrasah is considerably lower than that of graduates from the equivalent formal general and vocational education. Furthermore, graduates from lower and upper secondary madrasah are unable to increase their income in the labor market. Raising awareness of the quality of madrasah in Indonesia is an important point discussed in this study.